2008
DOI: 10.1097/md.0b013e318190f170
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Off-Label Use of Biological Therapies in Systemic Autoimmune Diseases

Abstract: In 2006, the Study Group on Autoimmune Diseases (GEAS) of the Spanish Society of Internal Medicine created the BIOGEAS project, a multicenter study devoted to collecting data on the use of biological agents in adult patients with systemic autoimmune diseases (SAD). The information source is a periodic surveillance of reported cases by a MEDLINE search (last update before this writing: December 31, 2007). The analysis included a total of 19 SAD and 6 biological agents. By December 31, 2007, the Registry include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(85 citation statements)
references
References 21 publications
0
80
0
5
Order By: Relevance
“…Different results were reported from the Study Group on Autoimmune Diseases (GEAS), who published an impressive rate of response in ABD using etanercept (96%), (Ramos-Casals et al, 2008). These contradictory results indicate that more studies need to be undertaken in order to assess etanercept in ABD.…”
Section: Anti -Tnf-α (Tumor Necrosis Factor) Agentsmentioning
confidence: 47%
“…Different results were reported from the Study Group on Autoimmune Diseases (GEAS), who published an impressive rate of response in ABD using etanercept (96%), (Ramos-Casals et al, 2008). These contradictory results indicate that more studies need to be undertaken in order to assess etanercept in ABD.…”
Section: Anti -Tnf-α (Tumor Necrosis Factor) Agentsmentioning
confidence: 47%
“…Although Merrill et al 12 showed no difference in primary or secondary end points between placebo and rituximab treatment over 52 weeks of treatment in patients with moderate-to severe SLE in the EXPLORER trial, other studies have shown more promising results. Ramos-Casals et al 8 in 2008 showed that the best results were observed in the use of rituximab for Sjögren's syndrome, SLE, and cryoglobulinemia. A recent review suggested that rituximab induces B-cell depletion in 95% of patients, and a significant reduction in disease activity is achieved with a relatively good safety profile in patients with SLE 7 However, there is always a difficulty in assessing the status of SLE patients and response rate in any research, given the heterogeneity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This poses multiple questions on when and how to use these agents, since there are no current recommendations or guidelines on their use in such circumstances. 8 B cells play important roles in the pathogenesis of autoimmune diseases such as rheumatoid arthritis, SLE, and Sjögren's syndrome. They exert their pathogenic effect by producing autoantibodies which target self antigens and induce inflammation and tissue injury, disrupting T cell tolerance, activating autoreactive memory T cells, attracting and activating dendritic cells, inhibiting regulatory T cells, and recruiting follicular B-helper T cells, among many other functions.…”
Section: Discussionmentioning
confidence: 99%
“…For TMA, high-dose steroids, intravenous immunoglobulin, and/or plasmapheresis may be tried (25,28). Case reports suggest a beneficial effect of rituximab, a monoclonal B cell-depleting antibody, in severe APS (52). A phase II trial has shown safety and tolerability of rituximab in patients with APS (53).…”
Section: Discussionmentioning
confidence: 99%